GIS-Driven Comparative Analysis of Multi-Hazard Risks in Rural Villages: Insights from Licin District, Indonesia - Welayaturromadhona; M Ardy Ardan; Agus Triono; Riska Laksmita Sari; Eriska Eklezia Dwi Saputri; Hadziqul Abror (Universitas Negeri Semarang, 2026)
In this study, the Geographic Information System (GIS) is used to assess the risk of multiple hazards in eight rural villages of Kecamatan Licin, Banyuwangi Regency, Indonesia. The study looks at six natural disasters, including floods, earthquakes, forest fires, droughts, volcanic eruptions, and landslides. It maps and classifies the level of risk using Digital Elevation Models (DEM), soil amplification factors, the Standardized Precipitation Index (SPI), and Kawasan Rawan Bencana (KRB) zonation. Weighted overlay and fuzzy logic were used to calculate the risk level of each village (low, medium, or high) with the standardized hazard factors. The results demonstrate that the risks are in very different locations. Tamansari and Kluncing villages are highly prone to multiple hazards, for instance, due to their proximity to volcanic zones, steep slopes, and floodplains. On the other hand, villages of Licin and Pakel have high risks from volcanic lahar and landslide. Villages that are close to the ground, like Banjar and Gumuk are more susceptible to flooding, while places that do not hold on to rain are more susceptible to drought. The study illustrates how risks can intersect. For example, 32% of the Tamansari area is at high risk for flooding, landslides, and volcanoes at the same time. The GIS-based framework provides useful information for selecting the best disaster prevention plans by encouraging tailored actions based on the peculiar risk profiles of each town. The results show the significance of spatial analysis to develop more disaster-resilient rural areas. This is in conformity with the Sustainable Development Goals for disaster risk reduction.